2016
DOI: 10.1038/onc.2015.453
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 regulates hepatic lipid homeostasis through SREBP

Abstract: Sterol regulatory element-binding proteins (SREBPs) are key transcription factors regulating cholesterol and fatty acid biosynthesis. SREBP activity is tightly regulated to maintain lipid homeostasis, and is modulated upon extracellular stimuli such as growth factors. While the homeostatic SREBP regulation is well studied, stimuli-dependent regulatory mechanisms are still elusive. Here we demonstrate that SREBPs are regulated by a previously uncharacterized mechanism through TGF-β activated kinase 1 (TAK1), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…We here found that the deteriorating effects of USP18 knockout on hepatic steatosis and insulin resistance in HFD mice can be abolished by reducing TAK1 activation with its inhibitor. On the contrary, other studies found that disruption of TAK1 exacerbates lipid metabolic disorders and causes tumorigenesis in hepatocytes . The underlying reasons for these conflicting results are still unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We here found that the deteriorating effects of USP18 knockout on hepatic steatosis and insulin resistance in HFD mice can be abolished by reducing TAK1 activation with its inhibitor. On the contrary, other studies found that disruption of TAK1 exacerbates lipid metabolic disorders and causes tumorigenesis in hepatocytes . The underlying reasons for these conflicting results are still unknown.…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, other studies found that disruption of TAK1 exacerbates lipid metabolic disorders and causes tumorigenesis in hepatocytes. (38)(39)(40) The underlying reasons for these conflicting results are still unknown. It is possible that TAK1 plays essential roles in various physiological and pathological processes and that both total ablation and hyperactivation of TAK1 can induce severe hepatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…(29) Furthermore, our results showed that suppressing TAK1 activation with a specific inhibitor ameliorated insulin resistance, hepatic steatosis, and inflammation in mice fed a HFD diet, highlighting the causal role of TAK1 hyperactivation in glucolipid metabolic dysfunction in the liver. Intriguingly, other studies have verified an essential role of TAK1 in maintaining functional homeostasis of the liver, as indicated by exacerbated lipid metabolic disorders (30) and hepatic tumorigenesis (31) in TAK1-HKO mice. This inconsistency may be due to the diverse functionality of TAK1 in basal physiological processes.…”
Section: Discussionmentioning
confidence: 94%
“…The activation of these downstream signaling factors produces cytokines while maintaining cell viability and lipid metabolism during inflammation 21, 22 . TAK1, similar to caspases and RIPK3, is known to be targeted and inhibited by pathogens 23 .…”
Section: Introductionmentioning
confidence: 99%